Compulsory English Online Learning Practices in Melawi Regency; Implementations, Challenges and Potentials for Future Improvement - Muhammad Iqbal Ripo Putra (IKIP PGRI Pontianak, 2020)
This study aims to determine the practice of online learning in urban and rural areas in Melawi Regency. This study involved schools located in urban and rural areas. This study uses a descriptive type of research with a qualitative approach. Collecting data using semi-structured interviews, with interview tools using interview guidelines. In this study there were 3 schools involved, where 2 schools were in urban areas, 1 school was in rural areas, each school had 5 informants, the number of informants was 15 people, consisting of 1 principal, 2 English teachers, and 2 students. The findings of this study indicate the process of online learning practices that exist in urban and rural areas. Furthermore, the thematic analysis and cross-case analysis used show that the application of online learning has differences in each application in 3 schools in urban and rural areas, namely using full online learning and hybrid learning, namely online and offline modes, the obstacles faced are limited facilities, stability internet network and decreased student interest in learning. The potential for future improvements is the hope of support from the government to improve the obstacles faced in online learning in rural and urban areas in Melawi Regency.